2020
DOI: 10.4269/ajtmh.19-0290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Irrigation Schemes and Seasonality on Transmission Dynamics of Opisthorchis viverrini in the Snail Intermediate Host, Bithynia siamensis goniomphalos in Rice Paddy Fields in Northeast Thailand

Abstract: Opisthorchis viverrini is a fish-borne zoonotic trematode that causes significant public health problems in Southeast Asia. Its life cycle requires Bithynia snails as the first intermediate hosts, fish, and human and/or carnivore hosts. This study assessed impacts of land use practice for rice cultivation and seasonality on the transmission dynamics of O. viverrini in Bithynia siamensis goniomphalos in rice paddy field habitats. The transmission of O. viverrini cercariae in B. s. goniomphalos was monitored at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…The patterns of rainfall were consistent between years while the duration of irrigation and amount of irrigated water varied during the study period as previously reported (Kopolrat et al ., 2020) (Fig. 1).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The patterns of rainfall were consistent between years while the duration of irrigation and amount of irrigated water varied during the study period as previously reported (Kopolrat et al ., 2020) (Fig. 1).…”
Section: Resultsmentioning
confidence: 97%
“…The study area was a rice paddy-field habitat of B. s. goniomphalos in Sakon Nakhon Province, northeast Thailand, the same area as discussed in our previous report where detailed ecology and land-use practices in paddy rice cultivation were described (Kopolrat et al ., 2020). The area has a tropical monsoon climate with the year being divided into three seasons.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the informal nature of fish-distribution networks makes it challenging to impose food safety controls [7]. Controlling snail populations is also considered unfeasible as Bithynia snails inhabit many water sources, including rice paddies, and are resilient to cycles of drought and flooding [8,9]. Defecation into water sources occurs as fishermen and rice farmers work far from their homes for long periods of time [10].…”
Section: Interventions To Reduce Transmissionmentioning
confidence: 99%